Human papillomavirus genotyping on Reunion Island: A cross-sectional study of stored tissue samples. (September 2020) - Tran, Phuong Lien; Zafindraibe, Norosoa; Ah-You, Nathalie; Fernandez, Carla; Arrivets, Pascaline; Gérardin, Patrick; Michault, Alain; Boukerrou, Malik; Bertolotti, Antoine
Abstract: Objective: We aim to illustrate and evaluate the prevalence and distribution pattern of cervical human papilloma virus (HPV) genotypes on La Réunion Island, a French overseas territory, with the aim to guide future vaccination policies. Study design: Between January 2008 and July 2012, files of women undergoing gynaecological examination were retrospectively evaluated at the University Hospital, Reunion Island. Inclusion criteria required cervical biopsies with histopathological diagnosis of high-grade lesions or cancer and ASCUS Pap Smears (atypical squamous cells undetermined significance) results. The INNO-LIPA HPV Genotyping Extra® test was used for HPV genotyping. Results: A total of 401 ASCUS Pap Smears and 94 cervical biopsies were analyzed, of which 162 smears and 63 biopsies were HPV DNA positive (40.4 % and 67 % respectively). Detailed breakdowns of HPV genotype-specific distribution reported prevalence of HPV 16, 31, 33, 51 and 52. Of the 63 HPV-positive biopsies, 61 (96.8 %) contained at least one HPV genotype that is contained in the 9-valent HPV vaccine. The incremental preventable fraction of HPV infections that could have been added by the new 9-valent vaccine to the current bivalent vaccine was estimated at 26.2 %. Conclusions: Immunization with 9-valent vaccine should be effective, and in the long term, may reduce cervical cancer incidence in Reunion Island. Nevertheless, vaccination rates and coverage need to be maintained and improved.